In-hospital outcomes of ST elevation myocardial infarction in post-COVID-19 patients - M. G. Chashchin; A. V. Strelkova; A. Yu. Gorshkov; O. M. Drapkina (Российский кардиологический журнал)
Aim. To study clinical and anamnestic data, as well as inhospital outcomes in patients with ST elevation myocardial infarction (STEMI) with prior coronavirus disease 2019 (COVID-19) compared with previously uninfected STEMI patients.Material and methods. This prospective study included 181 patients treated for STEMI. The patients were divided into 2 groups, depending on the anti-SARS-CoV-2 IgG titer as follows: the main group included 62 seropositive patients, while the control group — 119 seronegative patients without prior COVID-19. Anamnesis, clinical and paraclinical examination, including electrocardiography, echocardiography, coronary angiography, were performed. Mortality and incidence of STEMI complications at the hospital stage were analyzed.Results. The mean age of the patients was 62,6±12,3 years. The vast majority were men (69,1% (n=125)). The median time from the onset of COVID-19 manifestations to STEMI was 60,00 [45,00; 83,00] days. According to, the patients of both groups were comparable the severity of circulatory failure (p>0,05). Coronary angiography found that in patients of the main group, Thrombolysis In Myocardial Infarction (TIMI) score of 0-1 in the infarct-related artery was recorded much less frequently (62,9% (n=39) vs, 77,3% (n=92), p=0,0397). Patients of the main group demonstrated a lower concentration of leukocytes (9,30*109/l [7,80; 11,40] vs 10,70*109/l [8,40; 14,00], p=0,0065), higher levels of C-reactive protein (21,5 mg/L [9,1; 55,8] vs 10,2 mg/L [5,1; 20,5], p=0,0002) and troponin I (9,6 ng/mL [2,2; 26,0] vs 7,6 ng/mL [2,2; 11,5], p=0,0486). Lethal outcome was recorded in 6,5% (n=4) of cases in the main group and 8,4% (n=10) in the control group (p=0,6409). Both groups were comparable in terms of the incidence of complications (recurrent myocardial infarction, ventricular fibrillation, complete atrioventricular block, stroke, gastrointestinal bleeding) during hospitalization (p>0,05).Conclusion. Patients with STEMI after COVID-19, despite a more burdened history and higher levels of C-reactive protein and troponin I, compared with STEMI patients without COVID-19, did not differ significantly in clinical status, morbidity, and inhospital mortality.